Розвиток рідної мови в українській діаспорі - Зорін, М. Т.; Міхальов, Б. С. (ХНУРЕ, 2019)
The article tells about an origin of the Ukrainian diasporas, importance to save culture and language, and also retention of history and traditions. In the conditions of adaptation to a new residence, culture and language there is a risk completely to assimilate. Pledge of national identity is correct education